A protocol for the generation of xeno-free, cGMP-compliant patient-specific iPSCs from skin biopsy - Wiley, Luke A. (Curr Protoc Stem Cell Biol, 2017)
This unit describes protocols for the generation of clinical-grade patient-specific induced pluripotent stem cell (iPSC)-derived retinal cells from patients with inherited retinal degenerative blindness. Specifically, we describe how using xeno-free reagents in an ISO class 5 environment, one can isolate and culture dermal fibroblasts, generate iPSCs and derive autologous retinal cells via 3D differentiation. The universal methods described herein for the isolation of dermal fibroblasts, and generation of iPSCs can be employed regardless of disease, tissue or cell type of interest.